Nerve-Highlighting Fluorescent Contrast Agents for Image-Guided Surgery - Summer L. Gibbs-Strauss; Khaled A. Nasr; Kenneth M. Fish; Onkar Khullar; Yoshitomo Ashitate; Tiberiu M. Siclovan; Bruce F. Johnson; Nicole E. Barnhardt; Cristina A. Tan Hehir; John V. Frangioni (Molecular Imaging)
Nerve damage is the major morbidity of many surgeries, resulting in chronic pain, loss of function, or both. The sparing of nerves during surgical procedures is a vexing problem because surrounding tissue often obscures them. To date, systemically administered nerve-highlighting contrast agents that can be used for nerve-sparing image-guided surgery have not been reported. In the current study, physicochemical and optical properties of 4,4‘-[(2-methoxy-1,4-phenylene)di-(1 E )-2,1-ethenediyl]bis-benzenamine (BMB) and a newly synthesized, red-shifted derivative 4-[(1 E )-2-[4-[(1 E )-2-[4-aminophenyl]ethenyl]-3-methoxyphenyl]ethenyl]-benzonitrile (GE3082) were characterized in vitro and in vivo. Both agents crossed the blood-nerve barrier and blood-brain barrier and rendered myelinated nerves fluorescent after a single systemic injection. Although both BMB and GE3082 also exhibited significant uptake in white adipose tissue, GE3082 underwent a hypsochromic shift in adipose tissue that provided a means to eliminate the unwanted signal using hyperspectral deconvolution. Dose and kinetic studies were performed in mice to determine the optimal dose and drug-imaging interval. The results were confirmed in rat and pig, with the latter used to demonstrate, for the first time, simultaneous fluorescence imaging of blood vessels and nerves during surgery using the FLARE™ (Fluorescence-Assisted Resection and Exploration) imaging system. These results lay the foundation for the development of ideal nerve-highlighting fluorophores for image-guided surgery.